Characterization of Sphingomyelin Phosphodiesterase Expression in Bumblebee (Bombus lantschouensis). Issue 5 (26th October 2018) - Han, Lei; Ding, Guiling; Liu, Yanjie; Huang, Jiaxing; Wu, Jie
Abstract: Sphingomyelin phosphodiesterase ( SMPD ) is a hydrolase that plays a major role in metabolic reactions involving sphingomyelin. Here, we describe an analysis of the cDNA sequence and gene structure of SMPD in bumblebee ( Bombus lantschouensis ). The expression of SMPD in different tissues and at different developmental stages and reproductive statuses was examined by real-time polymerase chain reaction (PCR). The results showed that the SMPD cDNA has a length of 2000 bp and contains an open reading frame (ORF) of 1, 801 nucleotides that encodes a polypeptide of 599 amino acids. The full-length SMPD gene is 4228 bp and contains eight exons and seven introns. A comparative analysis revealed that the SMPD gene sequence in B. lantschouensis shares high sequence identity with those in other Bombus species. The SMPD gene is expressed broadly in various tissues and presents higher transcript levels in the ovary, midgut, and epidermis and thoracic tissues. Among the different developmental stages, the highest expression of SMPD was detected at the Pw pupal stage (pupae with an unpigmented body cuticle and white eyes), and the expression of this gene decreased from the Pp (pupae with pink eyes) to the Pdd (dark-eye pupae with a dark-pigmented cuticle) stages. In addition, SMPD expression was significantly upregulated after female egg laying. In conclusion, our results show that the bumblebee SMPD gene might play a key role at the Pw developmental stage and in female oviposition.